English Teachers’ Perception on the Implementation of Merdeka Curriculum at Private Vocational High School - Intan Safitri; Etika Dewi Kusumaningtyas (Universitas An Nuur, 2023)
Curriculum is a set of plans and tools to establish the objectives, subject matter, and curriculum material as well as the learning activities to be carried out in order to achieve particular educational goals. This research was conducted to ascertain English teachers’ perception of the implementation of the Merdeka curriculum in one of the vocational high schools, called Centers of Excellence (SMK PK). The researcher used a descriptive qualitative method as a research design, and data obtained through observation and interview. The subjects were four English teachers. This research is focused on the following six areas of implementation Merdeka Curriculum: 1) Understanding of subject 2) Content administration reduction in MBKM 3) Learning process and P5 in MBKM 4) Assessment 5) Teacher experience in MBKM 6) Obstacles. The results of the research found that the Merdeka curriculum in one of the vocational high schools had been implemented. However, an obstacle arose related to teacher are still adapting to the new term in the Merdeka curriculum. The teachers are unable to manage time effectively in the learning process and have limited references. The teachers must provide handling during the administration of the evaluation because the students are different, resulting in less engaged students for whom the teacher is only a facilitator. Other problems included teachers who rarely utilized the Merdeka curriculum's assessment methods. Additionally, the English teacher has a way to overcome some of the obstacles and make sure the Merdeka curriculum succeeds.